Conformational constraints in nuclear DNA. - Cook, P; Brazell, I (1976)
We have investigated DNA superstructure in a wide range of nuclei of higher cells by gently lysing cells to release structures that resemble nuclei but are depleted of nuclear proteins. The sedimentation properties of these structures, which we call nucleoids, have been examined in sucrose gradients containing the intercalating agent, ethidium. The sedimentation rate of nucleoids derived from the growing cells of mammals, birds, amphibians and insects varies in the manner characteristic of circular and superhelical molecules of DNA. These characteristic changes in sedimentation rate are abolished by irradiating the nucleoids with low doses of gamma-rays, a procedure known to introduce single-strand scissions into DNA. We have also investigated by similar means DNA superstructure in nucleoids derived from a variety of different chick cells. Nucleoids derived from adult hen erythrocytes differ from the other nucleoids studied in that their sedimentation rate does not vary in the manner characteristic of supercoiled DNA.